Evaluation of Nicotine Addiction in Adolescents - Fevzi Kahveci; Zehra Aycan (Güncel Pediatri)
Introduction: Those who start smoking during adolescence have a higher risk of developing an addiction. This study aimed to evaluate cigarette addiction in the adolescents who smoke. Materials and Methods: Cross-sectional, observational, single center study. Two hundred sixty middle and late-aged adolescents 14 years and over who presented to the adolescent and pediatric polyclinic and declared that they were smokers were included in the study. Results: In our study, 81 (31.2%) were female and 179 (68.8%) were male. The mean age of the 260 adolescents was 17.0±1.5 years. The mean age at the first attempt was 13.9±2.3 years, and the mean age of starting regular smoking was 14.2±2.1 years. The age range at which the adolescents started smoking the most was 14-17 years (73%). According to the mFTQ test, approximately 70% of the adolescents and 90% according to the HONC test were nicotine dependent. Addiction scores of late-age adolescence were higher. We found that although males smoked more by percentage, sex was not associated with addiction. According to both tests related to addiction used in our study, as the number of cigarettes increases (mFTQ test: p<0.0001; HONC test: p<0.001) addiction also increases. Conclusion: It was observed that there was a high rate of addiction among smokers. In addition, it was found that the age of starting smoking is low in our studyand the addiction increases as the age of starting smoking decreases.